Event-study methodology under conditions of event-induced variance - BOEHMER, Ekkehart (Institutional Knowledge at Singapore Management University, 1991)
Many authors have identified the hazards of ignoring event-induced variance in event studies. To determine the practical extent of the problem, we simulate an event with stochastic effects. We find that when an event causes even minor increases in variance, the most commonly-used methods reject the null hypothesis of zero average abnormal return too frequently when it is true, although they are reasonably powerful when it is false. We demonstrate that a simple adjustment to the cross-sectional techniques produces appropriate rejection rates when the null is true and equally powerful tests when it is false.